2000
DOI: 10.1093/emboj/19.3.370
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of rescue of common p53 cancer mutations by second-site suppressor mutations

Abstract: The core domain of p53 is extremely susceptible to mutations that lead to loss of function. We analysed the stability and DNA-binding activity of such mutants to understand the mechanism of second-site suppressor mutations. Double-mutant cycles show that N239Y and N268D act as 'global stability' suppressors by increasing the stability of the cancer mutants G245S and V143A-the free energy changes are additive. Conversely, the suppressor H168R is specific for the R249S mutation: despite destabilizing wild type, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
149
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(158 citation statements)
references
References 34 publications
7
149
0
2
Order By: Relevance
“…N239Y increases the thermodynamic stability of the p53 core domain by about 1.5 kcal mol Ϫ1 , which is able to restore wild type stability in G245S/N239Y (42). We observed that the N239Y mutation led to higher transcriptional and apoptotic activity in mammalian cells.…”
Section: Comparison Of P53 Levels and The Role Of Thermodynamicmentioning
confidence: 64%
“…N239Y increases the thermodynamic stability of the p53 core domain by about 1.5 kcal mol Ϫ1 , which is able to restore wild type stability in G245S/N239Y (42). We observed that the N239Y mutation led to higher transcriptional and apoptotic activity in mammalian cells.…”
Section: Comparison Of P53 Levels and The Role Of Thermodynamicmentioning
confidence: 64%
“…The mutations N239Y and N268D have been reported to restore transcriptional activity in a subset of cancer mutants, including G245S (36). Double-mutant cycles suggest that they act as global stability suppressors (37). As such, they mimic the effects of a hypothetical generic small-molecule drug.…”
Section: T-p53c-y220cmentioning
confidence: 99%
“…A prime example is the mutant R249S. Studies on second-site suppressor mutations have shown that full restoration of DNA-binding activity is found only in the presence of a mutation (H168R) that specifically reverses the structural changes induced by the oncogenic mutation (16,36,37).…”
Section: T-p53c-y220cmentioning
confidence: 99%
“…Unlike p63 and p73, human p53 DBD is extremely susceptible to mutational inactivation that lowers its thermodynamic stability (35). A second site suppressor mutation in p53, N268D, restores DNA binding activity by increasing the thermodynamic stability in some oncogenic mutants (35)(36)(37). The amino acid asparagine (Asn-268) in human p53 is not conserved and is substituted by aspartic acid in rat and mouse p53 and by arginine in chicken, Xenopus, and other species (38).…”
Section: Sch529074 Binds To P53 Core and Acts As A Chaperone-mentioning
confidence: 99%